104 Simulation to support system safety in a tertiary paediatric hospital. (30th November 2020) - Broughton, Emma
Abstract : Background: The Clinical Simulation Centre (CSC) at GOSH, now provide one of the largest in-situ simulation programmes in the region. Prioritising advancement of the patient safety agenda, we work closely with our Quality and Safety teams to embed key safety themes within out trust wide in- situ curriculum. A key objective of delivering simulation in-situ in the clinical setting; is to identify and mitigate against hidden risks or 'latent safety threats' in the clinical environment; which could cause unintended harm to patients or staff. Method: Over the past year, the CSC team have begun to expand the applications of the pan-trust in-situ programme to deliver a number of Systems Safety exercises. These simulations focus purely on rehearsal and refinement of process and systems, towards uncovering and mitigating against latent safety threats or gaps in practice. A reporting tool has been developed by the team; to capture risks |identify mitigating actions. Results: In recent months, the Covid-19 pandemic presented our teams with many new or unfamiliar working practices. This context further shifted our focus towards Systems Safety Simulations; with the aim of enabling our clinical teams to focus on rehearsing and preparing for new ways of working. These exercises delivered in partnership with clinical teams across the trust; successfully supported the development of 5 new clinical guidelines during the pandemic. In one exercise alone; 11 latent safety threats (LSTs) were captured and managed with the appropriate teams. LST themes included; availability of resources |Communication and co-ordination in PPE |Infection Prevention&Control risks | Environmental preparedness. Conclusion: These recent exercises have demonstrated the potential applications of simulation to support process improvement. Beyond the Pandemic, we aim to continue to deliver Systems Safety Simulation exercises to help make our clinical systems and spaces safer for patients and the teams who care for them.